Social environmental determinants of student dropout in the plantation settlement - Mohamed Irshana Rasmy; Sivapalan Selvadurai; Junaenah Sulehan (Penerbit Universiti Kebangsaan Malaysia, 2017)
The role of institutions in the social environment appears to be one of the important predictors of student’s attendance and academic performance and social development. Despite existing research on contributions of social environment factors namely home, social and school on student dropout but these factors were examined in a separate fashion and primarily focussed in rural villages. This study aims to develop a comprehensive framework of social environmental determinants of student dropout in secondary school in the the plantation settlement which is understudied. These determinants play a critical role in identifying the measures or interventions that will enhance a child’s education. The role of these institutions in the social environment and its influence on student dropout is examined in general and amongst the secondary school students in the plantation settlement in particular. The findings reveal that although family factors contribute predominantly to student dropout as shown in conventional literature, school and social variables appear to be equally important and emerging determinants as well. Implications to policy and intervention are also discussed.